The Learning of E-Sustainability Competences: A Comparative Study between Future Early Childhood and Primary School Teachers - Mayra Urrea-Solano; María J. Hernández-Amorós; Gladys Merma-Molina; Salvador Baena-Morales (MDPI AG, 2021)
Digital technologies play a key role in the fulfilment of the 2030 Agenda. However, their contribution to this goal depends on the digital culture of society. In this context, future teachers' knowledge of e-sustainability is of paramount importance, as the responsible and sustainable behaviour of future generations largely depends on their skills in this area. Therefore, this study aimed to identify the existence of possible differences in digital competences in sustainability among trainee teachers. The study involved the participation of 348 students in the 2nd year of their Bachelor's Degrees in Early Childhood and Primary Education at the University of Alicante (Alicante, Spain), who filled out a questionnaire on this topic. The SPSS v. 25 statistical programme, with which a comparative analysis was carried out, was used to process the data. On the basis of the results, the students of the Bachelor's Degree in Early Childhood Education generally presented a higher level of e-sustainable competences, especially with regard to general competences and the economic dimension of digital sustainability. Despite this, and given the small size of the differences, we conclude that there is a need to design didactic proposals to favour the acquisition of these competences among future teachers at both stages.